2013
DOI: 10.1186/2193-1801-2-90
|View full text |Cite
|
Sign up to set email alerts
|

Technical accuracy of optical and the electromagnetic tracking systems

Abstract: Thousands of operations are annually guided with computer assisted surgery (CAS) technologies. As the use of these devices is rapidly increasing, the reliability of the devices becomes ever more critical. The problem of accuracy assessment of the devices has thus become relevant. During the past five years, over 200 hazardous situations have been documented in the MAUDE database during operations using these devices in the field of neurosurgery alone. Had the accuracy of these devices been periodically assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Schicho et al tested the StealthStation R Treon R EM system and also found better results compared to the NDI Aurora R [162]. Koivukangas et al also performed a study with a StealthStation system, comparing EM and optical tracking, and found a slightly better accuracy for the latter [79].…”
Section: B Study Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schicho et al tested the StealthStation R Treon R EM system and also found better results compared to the NDI Aurora R [162]. Koivukangas et al also performed a study with a StealthStation system, comparing EM and optical tracking, and found a slightly better accuracy for the latter [79].…”
Section: B Study Resultsmentioning
confidence: 99%
“…In the context of accuracy assessment, a direct comparison of EM tracking to optical tracking would also be of interest, but, even though some authors tested both systems in clinical environments and found better results for optical tracking (e.g., [79,172], see Sec. 6-C), a similar standardized assessment for both technologies is not available.…”
Section: Discussionmentioning
confidence: 99%
“…A reference aluminum block with precisely drilled holes, which are detected by the mechanical and optical position tracker, serves as ground truth. Koivukangas et al [16] use a specially designed accuracy assessment phantom, a cube with high precision set assessment point, in order to evaluate the accuracy of optical tracking systems used in surgical area.…”
Section: Related Workmentioning
confidence: 99%
“…The electromagnetic tracking system (ETS) has been successfully used for surgical navigation and its technical accuracy to track motion has been investigated . It has to be admitted that the main focus of this study was to explore the direction rather than the magnitude of displacement.…”
Section: Discussionmentioning
confidence: 99%